New Paradigm of Learning in Southeast Asia: Pandemic and Online Learning Strategy - Transinata, Tatas; Aprilia, Yessi; Indah, Rini (Journal of Education for Sustainability and Diversity, 2023)
The Covid-19 pandemic has brought significant problems and changes to the education sector around the world, including in Southeast Asia. The learning process is a heavily impacted sector that requiring attention and strategies to overcome it. This study aims to explore how universities in Southeast Asia choose and implement online learning strategies and what learning theories are based on them. The research method used Systemic Literature Review based on the Scopus database. The object of research used articles from top ranking universities ASEAN, namely the Philippines, Malaysia, and Singapore. Researchers found 18 articles that had Online Learning coding, Method/Model and year 2019-2021. The findings from the research are 30 online learning models consisting of full online learning to hybrid learning. The application of this learning model also has 3 basic online learning theories, namely "Community of Inquiry" (CoI), Connectivism, and Online Collaborative Learning (OCL).